Chinese herbal medicine the formulas of Dr. John H. F. Shen - Hammer, Leon (Thieme, 2013)
A treasure trove of information for practitioners of Chinese medicine, this book gathers the herbal formulas of master practitioner Dr. John H. F. Shen for the first time. Not only does it incorporate the experience of Dr. Leon Hammer, who studied directly with Dr. Shen for nearly three decades, but it also presents the stimulus, rationale, and thinking behind many of the formulas. The result is a unique compendium of diseases spanning infancy to old age--with expert analysis and commentary by the authors--and the clinically tested herbal formulas used to treat each condition.Special Features Logically organized in two sections: the first by standard medical systems ranging from cardiovascular to respiratory; and the second by life cycle progression and developmental milestones Offers valuable insights on the etiology, symptoms, pathogenesis, and clinical signs of each disease Combines pulse diagnosis with herbal medicine for superior therapeutic outcomes Builds on the prominent Ding-Menghe lineage in Chinese medicine, dating back to the early 1600s Offering a window into the mind and practice of one of the greatest innovators in Chinese medicine, and integrating the knowledge and expertise of two foremost modern practitioners, this book is the only complete source available on Dr. Shens herbal heritage. It is essential reading for all Chinese medicine practitioners, herbalists, and other medical professionals prescribing herbs.